The Concept of Developing the Activity of Representative Bodies of Local State Authority and its Significance - Isomiddinov Eldor Botirovich (Scientific Trends, 2025)
The article provides the expected efforts to develop the activities of local state authorities in Uzbekistan, their implementation, and practical importance. It also talks about the concept of modernization of the self-government system, the development of the activities of the representative bodies of local state power, and the goals, plans, and reform measures envisaged in it.
Keywords: Local council, working group, public administration, legislative documents, people’s power, realization, control system, political regulation.